FIRST RECORD OF THE GENUS GRAPTOMYZA WIEDEMANN, 1830 (DIPTERA: SYRPHIDAE) FROM PAKISTAN - M. A. Hassan; I. Bodlah; M. Ahmad; A. R. Kayani; K. Mahmood (Journal of Animal and Plant Sciences, 2020)
The genus Graptomyza Wiedemann, 1820, is newly recorded from Pakistan. Two species of the genus are reported: Graptomyza flavonotata Brunetti, 1917 and Graptomyza brevirostris Wiedemann, 1820 for the first time from Pakistan. An identification key to these newly recorded species, their diagnostic characters, distribution, host plants and photographs are provided for the taxonomic study.
Keywords: First record; Graptomyza; Syrphidae; Oriental region; Pakistan